Measures with unique tangent measures in metric groups - Mattila, Pertti (MATHEMATICA SCANDINAVICA, 2005)
We show that a Radon measure on a locally compact metric group with natural dilations has almost everywhere a unique tangent measure if and only if it has almost everywhere a Haar measure of a closed dilation invariant subgroup as its unique tangent measure.